A Handbook of Wireless Telegraphy Its Theory and Practice, for the Use of Electrical Engineers, Students, and Operators - Erskine-Murray, James (Cambridge library collection. Technology, 1907)
James Erskine-Murray (1868–1927) was a Scots expert in wireless technology who studied under Lord Kelvin for six years at Glasgow University before arriving at Trinity College, Cambridge as a research student. He eventually became a telegraphy consultant and published this work in 1907. Its aim was to inform engineers, students, and radio operators about many aspects of a rapidly changing technology. The book covers recent developments of the time, and a whole chapter is dedicated to the issue of transmission. Erskine-Murray also provided a chapter of tables containing data which he calculated himself and which had not appeared in print before. The work stands as a classic in the field of early engineering texts, and offers contemporary students and radio enthusiasts a useful guide to early wireless technology